731. The Emergence of Mobile Colistin Resistance (mcr) Genes among Enteric Pathogens in the United States — 2008–2019. (31st December 2020) - Tobolowsky, Farrell A; Friedman, Cindy R; Ryan, Matthew; Birhane, Meseret; Chen, Jessica; Webb, Hattie E; Beukelman, Rachel A; Bokanyi, Rick; Byrd, David J; Connor, Diana; Hanna, Samir; Kimura, Akiko; et al.
Abstract: Background: Colistin, once seldom used clinically, has resurged as a "last resort antibiotic" for multidrug-resistant infections and is still used in animal agriculture in countries outside the United States. During 2015–2018, 8 plasmid-mediated, mobile colistin resistance genes ( mcr -1 to mcr -8) were each found in one or more clinical, animal, food, and environmental bacterial sources. We describe the epidemiology of mcr genes in enteric pathogens from US patients. Methods: State public health laboratories have performed whole-genome sequencing on enteric bacterial pathogens since 2015, and some have sequenced older isolates. We screened sequences of isolates collected through 2019 for mcr genes using a workflow based on ResFinder 3.0. State health officials interviewed patients for clinical and epidemiologic information, including demographics, hospitalization, and travel history. Results: We identified 41 patient isolates with mcr genes collected from stool, urine, and blood during 2008–2019. These included 37 nontyphoidal Salmonella (31 mcr -1, 6 mcr -3), 2 Vibrio (both mcr -4), and 2 Shiga toxin-producing E. coli (both mcr -1). The median patient age was 34 years (interquartile range: 24–54) and 54% were female. Of 23 patients with comorbidity data, 2 (9%) had immunodeficiency, 2 (9%) had past abdominal surgeries, and 1 (4%) had cancer. Patients sought care at doctor's offices (46%), emergency rooms (35%), and urgent care clinics (19%); 24% were hospitalized for the enteric illness. None died. Among 36 with information, 35 (97%) travelled internationally in the 12 months before illness; 30 (94%) of 32 traveled in the 7 days before. Only 4 (15%) of 27 had contact with a healthcare setting during their trip; common destinations were the Dominican Republic (35%), Vietnam (24%), Thailand (15%), and China (12%). Conclusion: The data strongly suggest that many patients acquired infection abroad. Nearly one in four were hospitalized, raising concerns that plasmids carrying mcr genes could spread among patients hospitalized with infections caused by multidrug-resistant pathogens for which colistin is the only available treatment. The acquisition of mcr genes by US travelers highlights the need for a global approach to antimicrobial stewardship. Disclosures: All Authors : No reported disclosures